Association between blood cadmium and vitamin D levels in the Yangtze Plain of China in the context of rapid urbanization. Issue 1 (5th January 2021) - Chen, Chi; Zhang, Hao-Jie; Zhai, Hua-Ling; Chen, Yi; Han, Bing; Li, Qin; Xia, Fang-Zhen; Wang, Ning-Jian; Lu, Ying-Li
Abstract: Background: China has experienced rapid urbanization in the past 30 years. We aimed to report blood cadmium level (BCL) in the rapidly urbanized Yangtze Plain of China, and explore the association between BCL and 25-hydroxyvitamin D (25(OH)D). Methods: Our data source was the Survey on Prevalence in East China for Metabolic Diseases and Risk Factors (SPECT-China) cross-sectional study (ChiCTR-ECS-14005052, www.chictr.org ). We enrolled 3234 subjects from 12 villages in the Yangtze Plain. BCLs were measured by atomic absorption spectrometry. 25(OH)D was measured with a chemiluminescence assay. Results: A total of 2560 (79.2%) subjects were diagnosed with vitamin D deficiency. The median (interquartile range) BCL was 1.80 μg/L (0.60–3.42) for men and 1.40 μg/L (0.52–3.10) for women. In women, mean 25(OH)D concentrations were inversely associated with BCL (0.401, 95% confidence interval: –0.697 to –0.105 nmol/L lower with each doubling of the BCL) after adjustment for age, educational status, current smoking, body mass index, diabetes, and season. However, there was no significant difference in 25(OH)D across the BCL tertiles for men. Conclusions: BCL in Chinese residents in the Yangtze Plain were much higher than that in developed countries. An inverse association between BCL and 25(OH)D was found in general Chinese women after multivariable adjustment. Future prospective cohort and animal studies are warranted to resolve the direction and temporality of these relationships, and to elucidate the exact mechanisms involved.